Translation control can shape TP53-dependent cell fate - Dario Rizzotto; Sara Zaccara; Annalisa Rossi; Erik Dassi; Alberto Inga (Molecular & Cellular Oncology, 2020)
The search for mechanisms underlying different cellular responses to the treatment with Nutlin-3, an MDM2 inhibitor that unleashes p53, revealed a translational control mechanism involving the RNA binding proteins PCBP2 and, particularly, DHX30. Sifting through a multi-functional p53-dependent transcriptional output, this translational control can modulate the activation of cell death pathways.